Performance evaluation of five Mediterranean species to optimize ecosystem services of green roofs under water-limited conditions. (15th April 2018) - Azeñas, V.; Janner, I.; Medrano, H.; Gulías, J.
Abstract: Rapid urban growth in Mediterranean cities has become a serious environmental concern. Due to this expansion, which covers adjacent horizontal ground, a critical deficit of green areas has been increasing. Moreover, irrigation is considered an important issue since water is one of the most limiting natural resources all over the world. The main objective of this study was to perform a long-term experiment to assess five Mediterranean species for extensive green roof implementation in Mediterranean-climate conditions. Brachypodium phoenicoides, Crithmum maritimum, Limonium virgatum, Sedum sediforme and Sporobolus pungens were grown in experimental modules under well-watered and water-limited conditions (irrigation at 50% and 25% ET0, respectively). Plant growth and cover, relative appearance, color evolution and water use were determined periodically for two years. Shoot and root biomass were quantified at the end of the experimental period. The effects of the irrigation treatments and seasonal changes were assessed to identify the advantages and disadvantages of each species according to their environmental performance. All species survived and showed adequate esthetic performance and plant cover during the experiment. S. sediforme registered the lowest variation of relative appearance along the experiment, the highest biomass production and the lowest water consumption. Nevertheless, B. phoenicoides appeared to be an interesting alternative to S. sediforme, showing high esthetic performance and water consumption throughout the rainy season, suggesting a potential role of this species in stormwater regulation related with runoff reduction. S. pungens performed well in summer but presented poor esthetics during winter. Highlights: S. sediforme, performed as the best species, (optimum growth and esthetic interest). B. phoenicoides, C maritimum, L. virgatum and S. pungens, provide a good performance under stressful conditions. B. phoenicoides showed good esthetic, and ability to reduce runoff. Studied species may optimize ecosystem services with deficit irrigation. S. pungens a C4, is constrained by the ability to survive in winter.